1997
DOI: 10.1577/1548-8675(1997)017<0206:msitqo>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Muskellunge Scale Interpretation: The Question of Aging Accuracy

Abstract: Age and growth data extracted from scales are often used when managing fish populations. However, accurate interpretation of scale annuli in certain species, such as muskellunge Esox masquinongy, has been suspect. The accuracy of age determination was tested with three experienced esocid scale readers who interpreted positive photo images made from acetate slide impressions projected on a microfiche reader. Images were made from scales of 25 known-age muskellunge (3-10 years old) from five Wisconsin lakes. Eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 2 publications
2
32
1
Order By: Relevance
“…A microfiche reader equipped with a 36-433 objective was used to interpret ages (Hoff and Serns 1986). We recognized the inaccuracies associated with aging muskellunge by scales (i.e., scale-based methods are notorious for underestimating true age; Fitzgerald et al 1997); however, we determined that the bias should be consistent between years and therefore concluded that the ages would be reflective of the true average age for sexually mature muskellunge of any given year. Because the fish were tagged, many individuals were observed multiple times during the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A microfiche reader equipped with a 36-433 objective was used to interpret ages (Hoff and Serns 1986). We recognized the inaccuracies associated with aging muskellunge by scales (i.e., scale-based methods are notorious for underestimating true age; Fitzgerald et al 1997); however, we determined that the bias should be consistent between years and therefore concluded that the ages would be reflective of the true average age for sexually mature muskellunge of any given year. Because the fish were tagged, many individuals were observed multiple times during the study.…”
Section: Methodsmentioning
confidence: 99%
“…Because the fish were tagged, many individuals were observed multiple times during the study. Therefore, scale interpretation for these fish was unnecessary because an earlier, presumably more accurate age estimate was available (Fitzgerald et al [1997] determined that age was more accurately estimated for younger muskellunge). This increased our confidence in the estimated ages, especially for older fish.…”
Section: Methodsmentioning
confidence: 99%
“…Nor can this method be used on species which cannot be reared in captivity prior to release. Nevertheless, this method has been used with success to confirm absolute age and growth increment formation at both the daily (Tsukamoto & Kajihara, 1987;Secor et al, 1995b) and the yearly scale (Fitzgerald et al, 1997;Svedang et al, 1998).…”
Section: Release Of Known Age and Marked Fishmentioning
confidence: 99%
“…In practice though, only a subset of the available methods possess the necessary precision. Release of known age or chemically-marked young-of-the-year (YOY) fish is well suited to this type of application (Ferrell et al, 1992;Fitzgerald et al, 1997). For annulus studies, modal progression with age subsampling is also straight forward and accurate; monitoring the modal length of the presumed YOY (for example, through periodic research surveys) confirms their identity as YOY, while inspection of the marginal increment in those same YOY in the season of annulus formation confirms the formation of the presumed first annulus (Ferrell et al, 1992).…”
Section: Validation Of the First Growth Incrementmentioning
confidence: 99%
“…Growth was also an important parameter but not included in our analysis after considering interpretation errors from scales resulting from irregular growth and resorption or erosion on the midlateral region (Casselman, 1990). Research on aging accuracy with muskellunge scales from Wisconsin (during the pike evaluation period) confirmed that scales were not reliable for accurate age estimation (Fitzgerald et al, 1997). Changes in esocid growth need to be determined using scale samples from younger fish (\8 years) and preferably in combination with the use of cleithra (Casselman, 1979;Casselman, 1996).…”
Section: Regulationsmentioning
confidence: 99%